2000
DOI: 10.1021/ja992755f
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise Charge Separation in Heterotriads. Binuclear Ru(II)−Rh(III) Complexes on Nanocrystalline Titanium Dioxide

Abstract: Two novel Ru(II)-Rh(III) polypyridine dyads, containing carboxylic functions at the Rh(III) unit, Rh III (dcb) 2 -(BL)-Ru II (dmp) 2 and Rh III (dcb) 2 -(BL)-Ru II (bpy) 2 (bpy ) 2,2′-bipyridine; dcb ) 4,4′-dicarboxy-2,2′-bipyridine; dmp ) 4,7-dimethyl-1,10-phenanthroline; BL ) 1,2-bis[4-(4′-methyl-2,2′-bipyridyl)]ethane), have been synthesized. Their photophysical behavior in solution, compared with that of the mononuclear Ru II (dcb) 2 (dmb) model (dmb ) 4,4′-dimethyl-2,2′-bipyridine), indicates the occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
74
0
2

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 65 publications
3
74
0
2
Order By: Relevance
“…The spectral profile of this band matches that of the Ru III,III 2 state [31] (Figure 3, inset), that is, the dinuclear ruthenium moiety is oxidized after excitation. In accordance with recent studies on TiO 2 sensitized by molecular dyads, [32,[51][52][53][54] we propose the following scheme for Ru III 3 ]-TiO 2 (e À ), which is characterized by a long lifetime of t 1/2 % 1 ms ( Figure 6) and for which the expected Ru III,III 2 ÀRu II,III 2 absorption difference (Figure 3) matches well the transient spectrum observed after 300 ns ( Figure 6). Although we can not precisely determine the rate constant for the second electron transfer, we can conclude that the rate lies in the range 10 9 > k > 10 7 s À1 , since its kinetic component is too fast to be resolved by nanosecond flash photolysis (resolution limit ca.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…The spectral profile of this band matches that of the Ru III,III 2 state [31] (Figure 3, inset), that is, the dinuclear ruthenium moiety is oxidized after excitation. In accordance with recent studies on TiO 2 sensitized by molecular dyads, [32,[51][52][53][54] we propose the following scheme for Ru III 3 ]-TiO 2 (e À ), which is characterized by a long lifetime of t 1/2 % 1 ms ( Figure 6) and for which the expected Ru III,III 2 ÀRu II,III 2 absorption difference (Figure 3) matches well the transient spectrum observed after 300 ns ( Figure 6). Although we can not precisely determine the rate constant for the second electron transfer, we can conclude that the rate lies in the range 10 9 > k > 10 7 s À1 , since its kinetic component is too fast to be resolved by nanosecond flash photolysis (resolution limit ca.…”
supporting
confidence: 90%
“…[47,55] It is also comparable to the slow recombination rates observed for previous systems with Ru-donor dyads as TiO 2 sensitizers. [32,[51][52][53][54] Note, however, that the ground-state recovery kinetics measured for 2 a and 2 b in the femto-to picosecond time domain do not show significant differences when going from solution to TiO 2 (data not shown), and this suggests that the primary electron injection is rather inefficient. Due to the multi-exponential character of these kinetics and poorer signal/noise ratio for the 2 a(2 b)-TiO 2 system it was impossible to precisely determine the injection efficiency, but it clearly does not exceed 10 %.…”
mentioning
confidence: 94%
“…Nazeeruddin et al have reported the "black dye" as promising charge transfer sensitizer in DSSC. Kelly, et.al studied other ruthenium complexes Ru(dcb)(bpy) 2 , Farzad et al explored the Ru(dcbH 2 )(bpy) 2 (PF 6 ) 2 and Os(dcbH 2 )(bpy) 2 -(PF6) 2 , Qu et al studied cis-Ru(bpy) 2 (ina) 2 (PF 6 ) 2 (Qu et al, 2000) , Shoute et al investigated the cis-Ru(dcbH 2 ) 2 (NCS) (Shoute et al, 2003), and Kleverlaan et al worked with OsIII-bpa-Ru (Kleverlaan et al 2000). Sensitizations of natural dye extracts such as shiso leaf pigments (Kumara et al, 2006), Black rice (Hao et al, 2006), Fruit of calafate (Polo and Iha, 2006), Rosella (Wongcharee et al, 2007), Natural anthocyanins (Fernando et al, 2008), Henna (Lawsonia inermis L.) (Jasim & Hassan, 2009;Jasim et al, in press 2011), and wormwood, bamboo leaves (En Mei Jin et al, 2010) have been investigated and photovoltaic action of the tested cells reveals some opportunities.…”
Section: Photosensitizermentioning
confidence: 99%
“…As linhas de pesquisa são as mais variadas e têm alcançado índices de impacto muito expressivos. Dentre os artigos mais citados no levantamento realizado no ISI, foram encontrados principalmente estudos nas áreas de nanomateriais magnéticos 28,29 , química e nanomateriais supramoleculares [30][31][32][33][34][35][36][37] , nanocompósitos de polímeros e óxi-dos de metais de transição (principalmente nanopartículas e óxidos lamelares) [38][39][40][41][42] , nanoencapsulamento 43 , nanotubos de carbono 44,45 ; filmes, interfaces e dispositivos 34,35,37,46,47 e células solares [48][49][50] . Essas contribuições são brevemente comentadas abaixo.…”
Section: Principais Linhas E Contribuiçõesunclassified
“…Tiveram impacto significativo os trabalhos realizados pelo grupo de Toma e Araki 34,35,37,46,47 envolvendo a aplicação de filmes de meso-tetra(piridil)porfirinas coordenadas a complexos de rutênio polipiridinas ou clusters trigonais de acetato de rutênio como materiais ativos de sensores de espécies tais como sulfito, nitrito, ácido ascórbico e oxigênio, bem como os trabalhos relacionados com células fotoeletroquímicas de Grätzel. Kleverlaan e colaboradores 48 estudaram as propriedades fotofísicas de complexos binucleares de rutênio e ródio bipiridina em solução, bem como adsorvido na superfície de um filme nanocristalino de TiO 2 . O estudo do processo de injeção de elétrons mostrou que cerca de 1/3 das espécies no estado excitado realizam diretamente esse processo, mas as demais injetam elétrons somente após uma reação de transferência de elétrons intramolecular envolvendo a formação da espécie Rh(II)-Ru(III).…”
Section: Figura 2 A) Gráficos Mostrando O Número De Publicações E B)unclassified